(untitled) (Conferencea, 2023)
This article is written about the present state of the archive buildings. As we mentioned above, it is important to make good use of life experiences in any country, especially the treasure that is considered a huge treasure, an incomparable source - always being aware of historical events, events that happened once, news that occurred, and scientific achievements. you have to stand. And such a huge treasure is stored in the so-called archive for centuries. Of course, collecting rare manuscripts whose history goes back to several centuries, unique documents related to the life activities of a person or the fields of production, scientific and cultural activities carried out in their time, processing them in order to pass them on to the next generations. especially important tasks such as storage are entrusted to the archives.